THE EFFECT OF PHYSICAL-CHEMICAL FACTOR OF LEACHATE NUTRITION SOLUTION OBTAINED FROM FRUIT WASTE BIOCONVERSION BY BLACK SOLDIER FLY (Hermetia illucens (L.) (DIPTERA: STRATIOMYDAE) ON PHAK COI (Brassica rapa L. cv. Nauli) IN NUTRIENT FILM TECHNIQUE HYDROPONIC SYSTEM - Danupermana, Afriansyah
Leachate that obtained from bioconversion of fruit waste by Black Soldier Fly larva (Hermetica illucens (L.)) can be an alternative to reduce production cost of cultivation using hydroponic method by substituting AB Mix fertilizer solution, either partially or entirely with leachate. The intention of this research is to determine how the physical-chemical of nutrition solution condition in a hydroponic Nutrient Film Technique (NFT) system that use leachate that are processed from Hermetia illucens larva bioconversion as a substitute source of hydroponic nutrition can affect pak choi (Brassica rapa L. cv. Nauli) growth rate and determine the best substitute nutrition solution based on plant height, number of leaves, plant wet weight, plant dry weight, chlorophyll total content, fiber content, and vitamin C content of Pak Choi. The composition variables of AB Mix and leachate are written as follows; treatment A(control) contains 100% AB Mix, treatment B contains 60% AB Mix and 40% leachate, treatment C contains 50% AB Mix and 50% leachate, treatment D contains 40% AB Mix and 60% leachate, and treatment E contains 100% leachate. The conclusion from physical-chemical parameter obtained are the average temperature of 24 0C for all treatment, dissolved oxygen average score of 8.85 mg/l, 8.65 mg/l, 8.43 mg/l, 8.45 mg/, and 8.38 mg/l, for treatment A, B, C, D, and E respectively, electrical conductivity average score of 2532.17 ?S/cm, 1728.17 ?S/cm, 1263.63 ?S/cm, 1011.50, and 606.33 ?S/cm for treatment A, B, C, D, and E respectively, and pH average score of 7.22, 7.98, 8.13, 8.18, and 8.32 for treatment A, B, C, D, and E respectively. Plant height and number of leaves parameter results obtained from treatment A, B, and C were not significantly different. Wet weight and dry weight parameter results obtained from treatment A and B were not significantly different. Treatment A has the highest chlorophyll total content of 10.49 mg/L, treatment C has the highest fiber content of 0.85%, treatment E has the highest vitamin C content of 92.21 mg/100 g sample. Based on this research, treatment B is the best substitute nutrition solution alternative that can be used it NFT hydroponic system for pak choy growth.